Динамика ксенофобии и антисемитизма в Украине (1994–2007) - Паниотто, В. (Социология: теория, методы, маркетинг, 2008)
The paper is devoted to the results of monitoring of ethnic prejudices of the population of Ukraine, which is conducting by the Kiev international institute of sociology every year since 1994. The data of 15 surveys, representative for the population of Ukraine, are analyzed. Each survey includes from 1500 up to 2000 respondents in the age 18+ (altogether about 28000 respondents). For measurement of a level of ethnic prejudices the scale of a social distance (Bogardus scale) was used. Xenophobia index is constructed on the base of factor analysis of social distances between population and different ethnic groups. As anti-Semitism index the social distance from Ukraine population to Jews is used. The essential factors influencing a level of Xenophobia and anti-Semitism are almost the same. The main factors are a place of residing (in a village a level of anti-Semitism is higher, than in the cities) and educational level (the higher educational level — the lower level of anti-Semitism). The age however influence the Xenophobia and anti-Semitism in different ways. The more age — the more level of Xenophobia. Respondents of age 18-20 have the lowest level of Xenophobia among age groups, but have the highest level of anti-Semitism. The results of research show that the indexes of xenophobia and anti-Semitism in Ukraine were growing from 1994 to 2007.